Synthesis and characterization of new imine liquid crystals based on terminal perfluoroalkyl group - Mohamed A. El-Atawy; Alaa Z. Omar; Mohammed L. Alazmi; Mai S. Alsubaie; Ezzat A. Hamed; Hoda A. Ahmed (Heliyon, 2023)
New organic derivatives named, (E)-3(or4) -(alkyloxy)-N-{(trifluoromethyl)benzylidene}aniline, 1a-f, were synthesized and examined their liquid crystalline behaviors. FT-IR, 1H NMR, 13C NMR, 19F NMR, elemental analyses and GCMS were used to validate the prepared compounds' chemical structures. We used differential scanning calorimetry (DSC) and polarized optical microscopy (POM) to investigate the mesomorphic characteristics of the formed Schiff bases. All tested compounds of series 1a-c have mesomorphic behaviour of nematogenic temperature ranges while the group 1d-f show non-mesomorphic properties. Moreover, it was found that the enantiotropic N phases included all of the homologue 1a-c. Computational studies using DFT (density functional theory) validated the experimental mesomorphic behavior results. All the analyzed compounds had their dipole moments, polarizability, and reactivity characteristics explained. Theoretical simulations showed that as the length of the terminal chain is increased, the polarizability of the stuided compounds increases. Consequently, compounds 1a and 1d have the least polarizability.